IDDF2022-ABS-0257 Endoscopic dilation with bougie versus balloon dilators for caustic-induced esophageal strictures. (2nd September 2022) - Singh, Anupam Kumar; Reddy, Yalaka Rami; Gupta, Pankaj; Shah, Jimil; Singh, Saroj Kant; Kochhar, Rakesh
Abstract : Background: Endoscopic dilation is the preferred initial management strategy for caustic-induced esophageal strictures (ES). However, the differences in the outcome of different dilators are not clear. Methods: Between January 1998 and December 2016, data of all the patients with caustic-induced ES was retrieved. Data collected included demographic parameters, type and intention of caustic substance ingestion, number of strictures, number of dilations required to achieve ≥14 mm, post-dilation recurrence and complications. Patients were divided into 2 groups based on the type of dilator used for stricture dilation, i.e., bougie dilator (Savary Gilliard) or balloon dilator (Controlled radial expansion, Boston Scientific Corp). Outcomes studied were technical success, clinical success (short-term and long-term), refractory and recurrent strictures, use of adjunctive therapy and complications. The two groups were compared for baseline parameters, technical and clinical success, proportion of refractory strictures, recurrence rates after initial success and adverse events. Technical success was achieved if stricture was dilated till ≥14 mm. Short-term clinical success was absence of dysphagia at 1 month after technical success while long-term clinical success was ability to maintain normal weight and ≤ grade 1 dysphagia without further dilatation. Results: 189 patients were included in the study with a mean age of 32.17±12.12 years and 119 (62.9%) being males. 122 (64.5%) patients underwent stricture dilation using bougie dilators while 67 (35.5%) with balloon dilators. Technical success was higher for bougie dilators compared to balloon dilators (90.1% vs 68.7%, p < 0.001). Short-term (65.6% vs 46.3%, p = 0.01) as well as long-term clinical success (86.9% vs 64.2%, p < 0.01) was better with bougie dilators. Multivariate analysis identified use of bougie dilators (aOR 4.868, 95% CI: 1.027 – 23.079), short-term clinical success (aOR 5.785, 95% CI: 1.203 – 27.825) and refractory strictures (aOR 0.151, 95% CI: 0.033 – 0.690) as independent predictors of the long-term clinical success. 24 (12.7%) patients developed adverse events with perforation in 21 (11.1%). Adverse events were similar for the two groups. Conclusions: The use of bougie dilators is associated with better clinical success in caustic-induced ES compared to balloon dilators.